Unrepaired Tetralogy of Fallot with Major Aortopulmonary Collateral Arteries in an Adult Patient. (18th December 2011) - Antonetti, Illena; Lorch, Daniel; Coe, Brian; Maxey, Thomas S.; Nallamshetty, Leelakrishna; Dadlani, Gul H.; Berlowitz, Michael S.; Cohen, Adam J.; Guglin, Maya E.
ABSTRACT: Tetralogy of Fallot is characterized by a ventricular septal defect, a large, overriding aorta, subpulmonic stenosis, and right ventricular hypertrophy. These lesions can be associated with abnormal development of the pulmonary vasculature. This can include peripheral pulmonic stenosis, discontinuous pulmonary arteries, anomalous pulmonary venous return, and the development of aortopulmonary collateral vessels. Aortopulmonary collateral vessels develop to supply underperfused areas of the pulmonary bed and pose a unique and challenging problem at the time of surgical repair, which involves closure of the ventricular septal defect, relief of right ventricular outflow tract obstruction, maintenance of pulmonary valve competency when possible, and establishment of laminar pulmonary blood flow to all segments of the pulmonary bed. We describe a 36‐year‐old man with unrepaired tetralogy of Fallot with distinctive aortopulmonary collaterals, who underwent complete surgical repair with good outcome. Two‐dimensional echocardiogram, cardiac magnetic resonance imaging, and cardiac catheterization each provided vital details allowing a stepwise approach to defining his unique anatomy for surgical correction.